Renal amyloidosis: a hidden complication of celiac disease (a case report) - Zaineb Kaouiri; Ikram Ftaimi; Meryem Benbella; Rabia Bayahia; Loubna Benamar; Naima Ouzeddoun; Tarik Bouattar (The Egyptian Journal of Internal Medicine, 2024)
Abstract We report a case of a 36-year-old female with untreated celiac disease, exhibiting both digestive discomfort and extra-digestive symptoms, including anemia. She subsequently developed a nephrotic syndrome. Biopsy of the accessory salivary gland confirmed amyloid deposits, as indicated by positive Congo red staining. Esophagogastroduodenal fibroscopy revealed characteristic signs of celiac disease and ruled out lymphoma. Further etiological screening identified celiac disease as the only possible cause of the amyloidosis. Complete remission was achieved after 3 months on a gluten-free diet, with later laboratory assessments indicating the absence of nephrotic syndrome and hematological abnormalities.